Fostering creativity in the Islamic world: towards an effective Islamic creative industry - Ismail, Salina; Shaari, Muhammad Shakirin (Discovery Publication, 2015)
The world’s predominantly Muslim countries have long been lagging in their contribution in the creative industry.This is due to the lost of creativity and innovative traits in the Muslim communities.This paper provides conceptual and preliminary analysis on the actual situation of the Muslim com- pared to others in the world, points out to the reasons leading to the situation and suggest ways to foster creativity in the Muslim communities.Realizing the situation, understanding the problem and move towards the correct direction to cure the illness is the important prerequisite.